قضايا الجندر في المفهوم القرآني والحركة النسوية الأنثوية الراديكالية: دراسة تحليلية نقدية: The Gender Issues in the Qur'anic Perspective and the Radical Feminist Movement: An Analytical Studies - Mohamed Ismail, Mohamed Mursaleen; Abdullah, Mustaffa (Jurnal Usuluddin, 2023)
This research aims to clarify the concept of gender in the Quranic concept in general and in the radical feminist movements in particular. The research deals with the causes of the emergence of the gender issue in Western countries and holding of international conferences for it. The research also addresses currents of female feminist movements and their interest in the issue of gender. The research sheds light on the goals of gender and its effects on the Muslim community. The research focuses on highlighting the most prominent and dangerous views of the radical feminist movement in the issue of gender and the position of the Holy Qur’an on it, through an analytical and critical study in the light of the Holy Qur’an. The research reached a conclusion that clarifies the most important findings and the recommendations recommended by the researcher.